Implementasi Pemberdayaan dan Kualitas Sumber Daya Aparatur terhadap Efektivitas Organisasi di Kantor Camat Tarakan Barat - Wartono Wartono (Asian Journal of Multidisciplinary Research, 2026)
This study aims to analyze the implementation of employee empowerment and the quality of human resources in relation to organizational effectiveness at the West Tarakan Subdistrict Office, Tarakan City. The study originated from the observed gap between the public service targets set by the West Tarakan Subdistrict Office and the realities encountered in practice. Although various employee empowerment programs have been implemented by the Regional Civil Service Agency of Tarakan City, public complaints are still frequently reported regarding slow service processes, unfriendly attitudes of personnel, and overlapping authorities among divisions. This situation raises the question: Have the empowerment initiatives and human resource quality improvement efforts effectively enhanced the performance of government personnel? This concern motivated the researcher to conduct a more in-depth investigation into how employee empowerment and the quality of human resources influence the work effectiveness of personnel at the West Tarakan Subdistrict Office. This research employed a descriptive research design using quantitative data analysis supported by qualitative data analysis. Data were collected through in-depth interviews, observations, and documentation. The research informants consisted of 10 civil servant respondents working within the West Tarakan Subdistrict Office and five Village Administrative Offices under the jurisdiction of West Tarakan Subdistrict, excluding those holding functional positions. Informants were selected using purposive sampling until data saturation was achieved. The findings indicate that the implementation of employee empowerment has not been optimal due to the limited delegation of authority from leaders to operational staff. The quality of human resources remains suboptimal, particularly in terms of limited training opportunities and competency development programs. The effectiveness of employees' work is further constrained by an uneven distribution of workload among staff and inadequate supporting facilities and infrastructure. In conclusion, the implementation of employee empowerment and the quality of human resources in improving organizational effectiveness at the West Tarakan Subdistrict Office has not yet reached an optimal level. Several issues were identified, including weak managerial supervision and guidance, limited employee involvement in decision-making processes, the presence of forced or reluctant work attitudes, inadequate education and training, excessive workload, insufficient facilities and infrastructure, and the lack of an effective reward and punishment system.